“Challenging Borders: Susanna Kaysen’s Girl, Interrupted as a Subversive Disability Memoir” - Pascale Antolin (European Journal of American Studies)
This article analyses Susanna Kaysen’s Girl, Interrupted as a subversive memoir and “counter-diagnosis,” relying on disability studies, women studies and critical discourse analysis. Taking advantage of the metaphoric adjective “borderline” in her diagnosis of “Borderline Personality Disorder” (BPD), Kaysen constantly emphasizes borders and boundaries—whether topographic, mimetic or generic—in order to cross and transgress them all the better. To achieve her goal, she relies on two major strategies of subversion, that is, abjection and carnival—including humor, irony, “symbolic inversion” and grotesque images. Thereby, Kaysen questions not only her own diagnosis and preconceived ideas about madness—women’s madness in particular—and mental patients, but she also challenges her recovery and the conventional genre of the disability memoir.